Efficacy of bath‐psoralen and ultraviolet A therapy for mycosis fungoides – retrospective analysis of 62 cases. Issue 2 (26th July 2021) - Shintani, Yoichi; Nishida, Emi; Furuhashi, Takuya; Muramatsu, Shinnosuke; Kubo, Ryoji; Nakamura, Motoki; Watanabe, Shoichi; Masuda, Hideyuki; Ikumi, Kyoko; Matsumoto, Kazuhiko; Yamazaki, Sayuri; Morita, Akimichi
Abstract: Photochemotherapy with psoralen and ultraviolet A (PUVA) is widely used for refractory skin diseases. Bathwater delivery of 8‐methoxypsoralen (8‐MOPS) with subsequent UVA irradiation (bath‐PUVA) or oral administration of 8‐MOPS with UVA is used to treat mycosis fungoides. We retrospectively analyzed 62 patients with mycosis fungoides (8 stage IA, 30 stage IB, 5 stage IIB, 18 stage IIIA, and 1 stage IVA2) treated with bath‐PUVA at the Dermatology Clinic of Nagoya City University Hospital from November 2004 to December 2013. A complete response was achieved in 37 (59.7%) patients, a partial response was achieved in 16 (25.8%), and stable disease was achieved in 6 (9.7%). Progressive disease was observed in 3 (4.8%) patients. Almost all patients in stage IA/IB achieved a complete response. Of the 5 stage IIB patients, 2 achieved a partial response, 1 achieved stable disease, and 2 had progressive disease. The serum concentrations of soluble interleukin‐2 receptor and lactate dehydrogenase decreased significantly following treatment with bath‐PUVA ( p  < 0.001). We examined the risk factors of patients whose stage progressed despite PUVA treatment. A multivariate Cox regression analysis of risk factors associated with stage progression yielded a hazard ratio of 28.5 for stage IIb. Treatment with bath‐PUVA is highly effective in the early stages of mycosis fungoides, and partially effective in advanced stages.